2021
DOI: 10.3389/fonc.2021.729212
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Significant Efficacy of Pyrotinib in the Treatment of Extensive Human Epidermal Growth Factor Receptor 2-Positive Breast Cancer Cutaneous Metastases: A Report of Five Cases

Abstract: BackgroundBreast cancer (BC) is the most common tumor to develop cutaneous metastases. Most BCs with cutaneous metastasis are human epidermal growth factor receptor 2 (HER2)-positive subtypes. Although the molecular mechanisms of breast cancer metastasis to different sites and the corresponding treatment methods are areas of in-depth research, there are few studies on cutaneous metastasis.Case PresentationFive HER2-positive BC patients with extensive cutaneous metastases were treated with a regimen containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 52 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…In PHENIX trial, subgroup analyses of PFS indicated that pyrotinib plus capecitabine exhibited PFS benefit and significantly decrease recurrence risk compared with placebo plus capecitabine in patients with non-visceral metastases [ 17 ]. Wang et al reported the significant therapeutic effect of pyrotinib on cutaneous metastases of HER2-positive BC for the first time [ 25 ]. However, they have not further explored the efficacy and safety of pyrotinib on patients with visceral-metastases.…”
Section: Discussionmentioning
confidence: 99%
“…In PHENIX trial, subgroup analyses of PFS indicated that pyrotinib plus capecitabine exhibited PFS benefit and significantly decrease recurrence risk compared with placebo plus capecitabine in patients with non-visceral metastases [ 17 ]. Wang et al reported the significant therapeutic effect of pyrotinib on cutaneous metastases of HER2-positive BC for the first time [ 25 ]. However, they have not further explored the efficacy and safety of pyrotinib on patients with visceral-metastases.…”
Section: Discussionmentioning
confidence: 99%